Endogenous non-retroviral RNA virus elements in mammalian genomes - Horie, Masayuki; Honda, Tomoyuki; Suzuki, Yoshiyuki; Kobayashi, Yuki; Daito, Takuji; Oshida, Tatsuo; Ikuta, Kazuyoshi; Jern, Patric; Gojobori, Takashi; Coffin, John M.; Tomonaga, Keizo (Nature (London), 2010)
Viral 'fossils' in the genome DNA derived from endogenous retroviruses is a common ancestral feature in mammalian genomes. Until now retroviruses have been the only group of viruses known to have left a fossil record of this type, but now elements derived from Borna-like N (EBLN) sequences have been found in the genomes of humans, non-human primates, rodents and a species of ground squirrel. Bornaviruses are non-segmented, negative-strand RNA viruses that replicate in the nucleus of infected cells. In primates, the elements are very old, formed more than 40 million years ago, while squirrel EBLN sequences are a more recent introduction. The conservation of open reading frames of primate EBLNs, as well as their expression as mRNA, implies that they may function as a source of genetic novelty in their host. Until now, retroviruses have been the only group of viruses known to have left a fossil record, in the form of endogenous proviruses; those elements make up approximately 8% of the human genome. Elements homologous to the nucleoprotein gene of the non-retroviral bornavirus are now shown to exist in the genomes of several mammalian species; the results give insights into the role of bornavirus as a source of genetic novelty to its host. Retroviruses are the only group of viruses known to have left a fossil record, in the form of endogenous proviruses, and approximately 8% of the human genome is made up of these elements 1 , 2 . Although many other viruses, including non-retroviral RNA viruses, are known to generate DNA forms of their own genomes during replication 3 , 4 , 5 , none has been found as DNA in the germline of animals. Bornaviruses, a genus of non-segmented, negative-sense RNA virus, are unique among RNA viruses in that they establish persistent infection in the cell nucleus 6 , 7 , 8 . Here we show that elements homologous to the nucleoprotein (N) gene of bornavirus exist in the genomes of several mammalian species, including humans, non-human primates, rodents and elephants. These sequences have been designated endogenous Borna-like N (EBLN) elements. Some of the primate EBLNs contain an intact open reading frame (ORF) and are expressed as mRNA. Phylogenetic analyses showed that EBLNs seem to have been generated by different insertional events in each specific animal family. Furthermore, the EBLN of a ground squirrel was formed by a recent integration event, whereas those in primates must have been formed more than 40 million years ago. We also show that the N mRNA of a current mammalian bornavirus, Borna disease virus (BDV), can form EBLN-like elements in the genomes of persistently infected cultured cells. Our results provide the first evidence for endogenization of non-retroviral virus-derived elements in mammalian genomes and give novel insights not only into generation of endogenous elements, but also into a role of bornavirus as a source of genetic novelty in its host.